2019
DOI: 10.1002/jcp.28241
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis of survival‐associated alternative splicing signatures uncovers prognostic predictors for head and neck cancer

Abstract: Background Previous studies have shown that alternative splicing (AS) plays a key role in carcinogenesis and prognosis of cancer. However, systematic profiles of AS signatures in head and neck cancer (HNC) have not yet been reported. Methods In this study, AS data, RNA‐Seq data, and corresponding clinicopathological information of 489 HNC patients were downloaded from The Cancer Genome Atlas. Univariate and multivariate Cox regression analyses were performed to screen fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…However, the area under the curve (AUC) for the model was only 0.723. Further, four candidate genes (TPM1, CLASRP, PRRC1, and DNASE1L1) were screened out among the 42,849 alternating splicing events identified in 10,121 genes in another study, which built a prognostic prediction model with an AUC of 0.704 [ 31 ]. These results were much lower than the AUC of 0.963 in our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the area under the curve (AUC) for the model was only 0.723. Further, four candidate genes (TPM1, CLASRP, PRRC1, and DNASE1L1) were screened out among the 42,849 alternating splicing events identified in 10,121 genes in another study, which built a prognostic prediction model with an AUC of 0.704 [ 31 ]. These results were much lower than the AUC of 0.963 in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, systematic profiling of prognostic AS signatures has been reported in esophageal carcinoma, ovarian cancer, papillary thyroid cancer, gastrointestinal adenocarcinomas as well as head neck cancer (Lin et al, ; Mao et al, ; Zhu, Chen, & Yong, ). Noticeably, comprehensive analyses of AS events in head neck squamous cell carcinoma (HNSCC) have been reported and predictive models based on AS have been established as prognostic predictors with high performance (Liang et al, ; Xing, Zhang, & Tong, ). However, HNSCC is a heterogeneous group of epithelial malignancies with diverse etiologic factors, tumorigenic processes and treatment modalities, as exemplified by HPV infection as well as its roles between OSCC and oropharyngeal SCC (Chi et al, ; D'Souza et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Noticeably, comprehensive analyses of AS events in head neck squamous cell carcinoma (HNSCC) have been reported and predictive models based on AS have been established as prognostic predictors with high performance (Liang et al, 2019;Xing, Zhang, & Tong, 2019). However, HNSCC is a heterogeneous group of epithelial malignancies with diverse etiologic factors, tumorigenic processes and treatment modalities, as exemplified by HPV infection as well as its roles between OSCC and oropharyngeal SCC (Chi et al, 2015;D'Souza et al, 2017).…”
mentioning
confidence: 99%
“…In nonmuscle cells, TPM1 acts as a cell transformation inhibitor. Many of the splicing isoforms of TPM1, including the AT‐splicing variant of TPM1 were found in our analysis to be involved in various types of tumors, such as head‐and‐neck cancer, 39 esophageal cancer, 40 breast cancer, 41 and lung cancer 42 . At the same time, for the first time, we found that high expression of the steroid‐assisted regulatory gene CALCOCO1 AS RI was significantly associated with poor prostate cancer prognosis.…”
Section: Discussionmentioning
confidence: 50%